Internet and intranet security management risks and solutions - Janczewski, Lech, 1943-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2000)
In the last 12 years we have observed amazing growth of electronic communication. From typical local networks through countrywide systems and business-based distributed processing, we have witnessed widespread implementation of computer-controlled transmissions encompassing almost every aspect of our business and private lives. This book addresses issues of information security from the managerial, global point of view. The global approach allows us to concentrate on issues that could be influenced by activities happening on opposite sides of the globe.
Part IV. Security and the law -- 9. Electronic Mail, Employee Privacy and the Workplace -- 10. Protecting Personal Privacy in Cyberspace: The Limitations of Third Generation Data Protection Laws Such as the New Zealand Privacy Act 1993 -- About the Authors -- Index.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Title from PDF t.p. (viewed on June 26, 2010).
Keywords: Internet -- Security measures; Intranets (Computer networks) -- Security measures; Computers -- Access control; Cryptography; Electronic books